2016
DOI: 10.1007/bf03404728
|View full text |Cite
|
Sign up to set email alerts
|

Flight dynamics model for preliminary design of PrandtlPlane wing configuration with sizing of the control surfaces

Abstract: This paper deals with the evaluation of the flight dynamics response of aircraft with a PrandtlPlane configuration by means of simple models to be used during the preliminary design. The study is completed by method that allows an initial sizing of the elevator and the aileron in such the way adequate requirements can be achieved: this analysis becomes important when the control surfaces can be located in both the front and the rear wing. The flight dynamics model is carried out considering the aircraft rigid,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…In analogy with experimental results shown in Oliviero et al., 9 the elevators can be designed to be counter-rotating and generate a pure pitching moment: in this way, the pitch control effectiveness is improved and the variation of vertical force due to elevators deflection is minimized. This solution increases the safety of flight, as, for example, in the event of a low altitude pull up maneuver (landing aborted).…”
Section: Procedures For the Conceptual Design Of High-lift Devices Anmentioning
confidence: 87%
See 1 more Smart Citation
“…In analogy with experimental results shown in Oliviero et al., 9 the elevators can be designed to be counter-rotating and generate a pure pitching moment: in this way, the pitch control effectiveness is improved and the variation of vertical force due to elevators deflection is minimized. This solution increases the safety of flight, as, for example, in the event of a low altitude pull up maneuver (landing aborted).…”
Section: Procedures For the Conceptual Design Of High-lift Devices Anmentioning
confidence: 87%
“…In fact, although drag reduction is the main advantage of the PrP, other interesting benefits have been found for different aircraft categories. Previous studies have shown that the PrP has a smooth stall behavior and post-stall is characterized by only a partial reduction of maneuverability and controllability, 8 pitch control can be obtained by using counter-rotating elevators (on both front and rear wings) which can introduce a pitching moment without perturbation to lift, 9 the pitch damping is higher than in the case of a wing-tail configuration, with benefits in terms of comfort and safety. 10 In addition, as summarized in Cavallaro and Demasi 11 and Frediani et al., 12 the PrP configuration can be adopted for aircraft of very different dimensions, such as Light Sport Aircraft, ultra large airliners, freighter aircraft, 13 or “cryoplanes.” 14…”
Section: Introductionmentioning
confidence: 99%
“…Whereas all the models provide a poor estimation of b -derivatives, the flat fuselage model is much more accurate in predictingaderivatives, and hence its choice represents the best compromise for the conceptual design phase. As detailed by Oliviero et al (2016), the research activities carried out during the project "IDINTOS" have provided both numerical and experimental results concerning the aerodynamics and flight mechanics of the PrP configuration in subsonic flight (Cipolla et al, 2016). Given the data shown in Figure 5 (Oliviero et al, 2016), at trim condition (a = 1°, b = 0°), the following accuracy factors can be calculated:…”
Section: Flight Mechanic Analysis Through Vortex-lattice Methods In Subsonic Rangementioning
confidence: 99%
“…As detailed by Oliviero et al (2016), the research activities carried out during the project "IDINTOS" have provided both numerical and experimental results concerning the aerodynamics and flight mechanics of the PrP configuration in subsonic flight (Cipolla et al, 2016). Given the data shown in Figure 5 (Oliviero et al, 2016), at trim condition (a = 1°, b = 0°), the following accuracy factors can be calculated:…”
Section: Flight Mechanic Analysis Through Vortex-lattice Methods In Subsonic Rangementioning
confidence: 99%
See 1 more Smart Citation